Sustainable production technology of sweet potato in response to ecological and economical demands (International Journal of Agricultural Research, Innovation and Technology, 2025)
Ecological catastrophe in the form of climate change is not only an issue, but now it is a real problem faced by and threatening human civilization, especially in producing food based on cereals and grains. Fortunately, sweet potato has many advantages from its biological potential to withstand climate change; however, it is ignored by policymakers. Consequently, the advantages of biological potential are often not followed by economic benefits for the farmers who grow sweet potato.  So far, there has not been a clear regulation provided by policymakers to arrange sweet potato in food security or its agribusiness. Demand for fulfilling food domestically and to meet foreign markets, especially from Singapore, Hong Kong, Korea and Japan, stimulates farmers to increase production. Therefore, farmers have to be encouraged to undertake the sustainable sweet potato production technology leads to high productivity for current demand as well as for future prospective. The greener future technology is oriented to organic with low external input, by utilizing waste integrated with animal husbandry, as well as other sectors. Greener technology, ecologically sound and suitable for future civilization, is required to avoid climate change with low CO2 emissions.Int. J. Agril. Res. Innov. Tech. 15(1): 99-108, June 2025